Rocky Mountain high: an environmental history of Cannabis in the American West - Johnson, Nick, author; Fiege, Mark, advisor; Orsi, Jared, committee member; Howkins, Adrian, committee member; Carolan, Michael, committee member (Colorado State University. Libraries, 2014)
Drugs are plants, too. Every ounce of tobacco, cocaine, heroin, marijuana, alcohol, or even coffee consumed in the United States today is the result of a profound human-plant relationship. The history of these relationships tells us much about how these plants have figured into human history and the human condition. It also illuminates how these plants went from being coveted elements of seductive nature to their current status as controversial and illicit commodities. The general revulsion with which we currently approach drugs, the people who use them, and the plants that produce them has effectively obscured the important place of drugs and drug plants in history. Current histories of Cannabis in the United States treat it first and foremost as the drug marijuana. But by foregrounding the plant that produces it--Cannabis indica--I am able to highlight the many important relationships Americans formed with it throughout the twentieth-century American West, and what these relationships tell us about drug plants and their place in our society. Examining these relationships not only provides fresh insights into relations of race, class, and gender in American history, but it also sheds light on under-examined topics such as cross-cultural contact, the buildup of traditional knowledge, the development of unofficial agriculture and commodity chains, and on the basic desires shared and pursued by all humanity.